MUNASABAH SCIENCE OF THE QUR'AN - Daruhadi, Gagah (International Journal of Social Service and Research, 2024)
The rational science of the Qur'an is a branch of science that focuses on understanding the relationships, interconnectedness, and harmony between various verses in the Quran. In this paper, the author wants to explain the importance of Munasabah knowledge in studying or interpreting this Islamic holy book regardless of the pros and cons to the existence of this discipline. This study uses a qualitative-descriptive approach to collect data in the form of written or oral descriptions through media such as YouTube or video. Data analysis techniques are further described in this paper. In addition, case studies are also included to provide concrete examples of the application of the knowledge of the rational science in qualitative research, especially in analyzing the relationships and linkages between Quranic verses and their implications in classical interpretation. The results and conclusions in this research are that we are able to understand the meaning of rational science, find the relevance of rational knowledge to the study of the Qidri, and know the discourse around the opinions of scholars about rational science.